Nano-twinning and uncommon α´-martensite formation as a result of very high cycle fatigue of metastable austenitic stainless steel at 573 K. (1st July 2023) - Smaga, Marek; Sorich, Andreas; Daniel, Tobias; Beck, Tilmann; Kohler, Christopher; Soppa, Ewa; Speicher, Magdalena
Abstract: Microstructural changes were investigated regarding the existence of the true endurance limit of a cyclic loaded metastable austenitic stainless steel AISI 347 in the very high cycle regime at 573 K. The fatigue tests were performed in stress control with a stress load ration R = -1 using a servo-hydraulic testing system with a load frequency of 980 Hz. Local cyclic plastic deformation and slip bands formation were observed even in the specimens that achieved the endurance limit at 5 × 10 8 cycles. Moreover, in these specimens further microstructural effects like nano-twins and α´-martensite formation were detected by transmission electron microscopy. While nano-twin formation takes place in the bulk material, the α´-martensite nucleates at the specimen's surface. Therefore, the α´-martensitic transformation is not the main mechanism responsible for the true endurance limit observed in the investigated AISI 347 at 573 K. Graphical abstract: Image, graphical abstract